ANALISIS PERUBAHAN ALIH FUNGSI LAHAN MANGROVE DI BINUANGA BOLAANG MONGONDOW UTARA - Daud Yusuf; Rahmat Jaya Lahay; Heru Z Thalib; Ahmad Zainuri; Wa Ode Faridawaty; Dewi Wahyuni K Baderan; Ramli Utina; Hasim (LPPM Universitas Cipta Mandiri, 2024)
This study analyses changes in mangrove land conversion in Binuanga, North Bolaang Mongondow, and its impacts on the environment and society. Satellite imagery data showed a decrease in mangrove area of about 2 hectares between 2009 and 2019, caused by land conversion to agriculture and climate change. However, the 2019-2023 period shows a positive trend with an increase in mangrove area of around 11.9 hectares to 69.6 hectares. This was triggered by the development of mangrove tracking tourism that encourages nursery and replanting in degraded areas. This finding shows that mangrove damage is reversible. Key efforts to achieve this include Implementation of stricter regulations on land conversion, Increased public awareness on the importance of mangroves, Implementation of rehabilitation and reforestation programmes